PENERAPAN STRATEGI PEMBELAJARAN TUNTAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKn - Laia, Seliran (Universitas Nias Raya, 2025)
The background to the problem of this research is that students are less active in participating in the learning process and student learning outcomes are low. The aim of the research is to determine the application of comprehensive learning strategies to improve student learning outcomes in Civics subjects in class VIII SMP Negeri 2 Susua. This research uses the type of Classroom Action Research. The research subjects were 20 class VIII students. Student learning results show that in cycle I the average student score was 63.25, the number of students who completed was 8 people with a completion percentage of only 40%, while there were 12 students who did not complete with an incomplete percentage of 60%. In cycle II, the average score increased to 76.75, all 20 students completed with a completion percentage of 100%. The conclusion of the research is that implementing thorough learning strategies can improve student learning outcomes in Civics subjects in class VIII SMP Negeri 2 Susua. Researchers provide several suggestions, namely: 1) Teachers should apply thorough learning strategies to Civics subjects, because this strategy can activate students. 2) Students should always be active and directly involved in the learning process in each subject. 3) When conducting research, future researchers should plan for a longer time so that the research results obtained are more. The background to the problem of this research is that students are less active in participating in the learning process and student learning outcomes are low. The aim of the research is to determine the application of comprehensive learning strategies to improve student learning outcomes in Civics subjects in class VIII SMP Negeri 2 Susua. This research uses the type of Classroom Action Research. The research subjects were 20 class VIII students. Student learning results show that in cycle I the average student score was 63.25, the number of students who completed was 8 people with a completion percentage of only 40%, while there were 12 students who did not complete with an incomplete percentage of 60%. In cycle II, the average score increased to 76.75, all 20 students completed with a completion percentage of 100%. The conclusion of the research is that implementing thorough learning strategies can improve student learning outcomes in Civics subjects in class VIII SMP Negeri 2 Susua. Researchers provide several suggestions, namely: 1) Teachers should apply thorough learning strategies to Civics subjects, because this strategy can activate students. 2) Students should always be active and directly involved in the learning process in each subject. 3) When conducting research, future researchers should plan for a longer time so that the research results obtained can be maximized.